Effects of a communication training for oncologists on early addressing palliative and end-of-life care in advanced cancer care (PALLI-COM): a randomized, controlled trial - Harnischfeger, Nele; Rath, H.M.; Alt-Epping, Bernd; Brand, H.; Haller, K.; Letsch, A.; Rieder, Nicola; Thuss-Patience, Peter; Bokemeyer, C.; Bergelt, C.; Oechsle, Karin (ESMO open, 2022)
Introduction: In advanced cancer care, early communication about palliative care (PC) and end-of-life (EoL)-related issues is recommended, but is often impeded by physicians’ communication insecurities. We investigated the effect of a newly developed compact communication skills training ‘PALLI-COM’ on oncologists’ competencies to early address PC/EoL-related issues. Materials and methods: We conducted a randomized, controlled trial (RCT) with an intervention group (IG; 2 Â 90 min training) and a wait list control group (CG) at ﬁve sites. At two assessment points, participating oncologists led videotaped medical consultations with simulated patients (SPs) via a privacy compliant video conference platform. SPs were represented by trained actors. The taped conversations were rated for primary outcome (communication skills assessed by adapted COM-ON-checklist and COM-ON-coaching rating scales) by raters blinded for study group. Secondary outcomes included oncologists’ self-reported communication skills (Self-Efﬁcacy in Palliative Care Scale, Thanatophobia-Scale, Communication about End of Life Survey, study-speciﬁc items) as well as external rating of the SPs. Univariate analyses of covariance with baseline adjustment were used to analyze intervention effects. - Results: A total of 141 oncologists [age: mean (standard deviation) ¼ 32.7 (6.3) years, 60% female (nIG ¼ 73, nCG ¼ 68)] participated. Following intervention, the IG showed signiﬁcantly more improvement in four out of ﬁve assessed communication skills: ‘reacting to emotions and showing empathy’, ‘pointing out opportunities and giving hope’, ‘addressing the EoL’ and ‘explaining the concept of PC’. IG participants also improved more than CG participants in almost all secondary outcomes assessed by participants and SPs: oncologists’ self-efﬁcacy, attitudes towards caring for terminally ill patients, communication strategies and conﬁdence in dealing with PC/EoL-related issues as well as communication quality from the SPs’ perspective. - Conclusion: Findings indicate that the compact communication skills training PALLI-COM increases oncologists’ competencies in early addressing PC/EoL-related issues from different perspectives. Implementation in routine oncology residency might improve advanced cancer care by strengthening these communication skills.
Online verfügbar und Artikelversion: 7. November 2022
Gesehen am 13.03.2023